A uniplanar manipulator for precision acoustic studies - Kamisiński, T.; Flach, A. (Archives of Acoustics, 2006)
Directional studies of acoustic systems and acoustic transducers require considerable precisionof orientation combined with co-ordination of control and measurement processes. Thepaper describes a manipulator designed and built by the authors. The manipulator is so designedthat it allows a studied sample to be precisely rotated with a remote control of therotation angle. It makes it also possible to measure angle-dependent radiation and receptionpatterns of loudspeakers, microphones, antennas, noisy mechanisms etc. The method of controland data collection from the manipulator via an RS-232 port should also be noted. It isalso possible to communicate with the plain table through LAN.